Use of Nanocellulose extracted from grass for adsorption abatement of Ciprofloxacin and Diclofenac removal with phyto, and fish toxicity studies. (1st January 2021) - Shahnaz, Tasrin; Vishnu Priyan, V.; Pandian, Sivakumar; Narayanasamy, Selvaraju
Abstract: The present study deals with the adsorption of antibiotic Ciprofloxacin (CPXO) and anti-inflammatory agent Diclofenac (DCF) on Grass nanocellulose (GNC) extracted from Cyprus rotundas grass. The adsorbent GNC was characterised using various microscopic, elemental and spectroscopic analysis to monitor the physicochemical alterations of the surface before and after adsorption. The size of the converted nanocellulose was found to be 40–50 nm. The experimental measures influencing the adsorption of CPXO and DCF that were optimised are initial solution pH, GNC dosage, temperature and initial concentration of the adsorbate. Halsey isotherm model and pseudo-second order kinetic model agreed best with the experimental outcome for both the adsorbate. The maximum adsorption capacity of GNC were 227.223 and 192.307 mg/g for CPXO and DCF respectively. Phytotoxicity studies were performed using 6 different types of seeds to evaluate the effect of GNC treated effluent on plants. Similarly, acute fish toxicity on zebra fish analysis showed to have lesser mortality rate of the effluent after adsorption of CPXO and DCF on GNC. Graphical abstract: Image 1 Highlights: Grass Nanocellulose was extracted remove Ciprofloxacin, and Diclofenac. Characterisation was done with FESEM, FETEM, Raman, XRD, AFM and EDX. Adsorption capacity was 227.223 and 192.307 mg/g for CPXO and DCF respectively. Sorbate-sorbent interactions were analysed by isotherm, kinetic, and thermodynamic. Ecotoxicological assessment of seed and fish toxicity for CPXO and DCF was evaluated.